Ensemble Structure of the Highly Flexible Complex Formed between Vesicular Stomatitis Virus Unassembled Nucleoprotein and its Phosphoprotein Chaperone. Issue 13 (3rd July 2016) - Yabukarski, Filip; Leyrat, Cedric; Martinez, Nicolas; Communie, Guillaume; Ivanov, Ivan; Ribeiro, Euripedes A.; Buisson, Marlyse; Gerard, Francine C.; Bourhis, Jean-Marie; Jensen, Malene Ringkjøbing; Bernadó, Pau; Blackledge, Martin; et al.
Abstract: Nucleocapsid assembly is an essential process in the replication of the non-segmented, negative-sense RNA viruses (NNVs). Unassembled nucleoprotein (N 0 ) is maintained in an RNA-free and monomeric form by its viral chaperone, the phosphoprotein (P), forming the N 0 –P complex. Our earlier work solved the structure of vesicular stomatitis virus complex formed between an N-terminally truncated N (NΔ21 ) and a peptide of P (P60 ) encompassing the N 0 -binding site, but how the full-length P interacts with N 0 remained unknown. Here, we combine several experimental biophysical methods including size exclusion chromatography with detection by light scattering and refractometry, small-angle X-ray and neutron scattering and nuclear magnetic resonance spectroscopy with molecular dynamics simulation and computational modeling to characterize the NΔ21 0 –PFL complex formed with dimeric full-length P. We show that for multi-molecular complexes, simultaneous multiple-curve fitting using small-angle neutron scattering data collected at varying contrast levels provides additional information and can help refine structural ensembles. We demonstrate that (a) vesicular stomatitis virus PFL conserves its high flexibility within the NΔ21 0 –PFL complex and interacts with NΔ21 0 only through its N-terminal extremity; (b) each protomer of P can chaperone one N 0 client protein, leading to the formation of complexes with stoichiometries 1N:P2 and 2N:P2 ; and (c) phosphorylation of residues Ser60, Thr62 and Ser64 provides no additional interactions with N 0 but creates a metal binding site in PNTR . A comparison with the structures of Nipah virus and Ebola virus N 0 –P core complex suggests a mechanism for the control of nucleocapsid assembly that is common to all NNVs. Graphical abstract: Highlights: The N 0 –P complex is essential for VSV NC assembly. Complexes with stoichiometry 1N:2P and 2N:2P form depending on the conditions. P remains highly flexible within the complex. Phosphorylation of P (S60, T62, S64) provides no additional interaction with N 0 . Conserved assembly mechanism can be proposed on the basis of structure comparison.